2016
DOI: 10.1063/1.4958601
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Hjorth descriptor for lung sound classification

Abstract: Abstract.The air flow during the respiration process produces lung sound and provide information on lung health. Automatic lung sound recognition becomes one of the areas of interest to researchers in the field of biomedical signal processing. Signal complexity measurement becomes one of features extraction method for lung sound analysis. Some signal complexity measurement technique that is often used for example are entropy, fractal dimension, and high-order statistics. In this study conducted multiscale Hjor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 13 publications
0
32
0
1
Order By: Relevance
“…This method produced 30 features and later this would be reduced to 10 features. In a previous study, the use of Hjorth descriptors for the extraction of lung sounds showed promising accuracy (Rizal et al, 2015a;2015b). From the test result, the proposed method was shown to provide higher accuracy compared to previous research (Rizal et al, 2015b).…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…This method produced 30 features and later this would be reduced to 10 features. In a previous study, the use of Hjorth descriptors for the extraction of lung sounds showed promising accuracy (Rizal et al, 2015a;2015b). From the test result, the proposed method was shown to provide higher accuracy compared to previous research (Rizal et al, 2015b).…”
Section: Introductionmentioning
confidence: 78%
“…The Hjorth descriptor usage for lung sound analysis has been presented in some papers (Rizal et al, 2015a;2015b). In the paper by Rizal et al (2015a), the Hjorth descriptor was calculated on the entire signal and produced an accuracy of 77% for five classes of data.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations